RELATIONSHIP OF NUMERICAL LEARNING, LEARNING INSURANCE, AND ATTENTION OF PARENTS WITH LEARNING MATHEMATICS STUDENTS CLASS IX SMP - Aditya Nur Irawan; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The numerical ability of the student in doing mathematics protudent in doing mathematics pa320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320320blems is still lacking, students are less interested in mathematics subjects, and parents who are less attentive to the learning activities of children is suspected to be a factor that causes low student learning outcomes. This study aims to determine whether or not there is a positive and significant relationship between numerical ability, interest in learning, and attention of parents with the results of learning mathematics students IX Muhammadiyah Junior High School Imogiri (SMP Muhammadiyah 3 Imogiri) Even Semester of the academic year 2016/2017. SMP Muhammadiyah Imogiri Bantul Regency academic year 2016/2017 consists of 5 classes IXA has an average value of Midterm in the middle among the five existing classes. Data collection techniques used questionnaires and test methods. The data collection instrument used a questionnaire of interest in learning, questionnaire of parental attention, numerical ability test, and math learning result test. Test instrument research using validity test, reliability test. The prerequisite analysis test includes a normality test, linearity test, and independence test. Data analysis for hypothesis analysis using product-moment correlation analysis and multiple linear regression analysis. The results showed there was a positive and significant relationship between numerical ability, interest in learning, and attention of parents to the results of learning mathematics. At a significant level of 5% v1 = 3, v2 = 24 Fcount = 4,239506252 and Ftable = 3.01 so Fcount> Ftable with double correlation coefficient 0.588539061 and multiple regression equations are three variables namely Å¶ = -68, 39347489 + 0, 01603402 X1 + 0,9670728 X2 + 0,266553832 X3 relative contribution X1 = 56.21988%, X2 = 25,19377%, X3 = 18,58636% and effective contribution X1 = 19,47388%, X2 = 8, 72659%, X3 = 6,43792